2012
DOI: 10.1088/1748-6041/7/3/035006
|View full text |Cite
|
Sign up to set email alerts
|

MRI-based morphological modeling, synthesis and characterization of cardiac tissue-mimicking materials

Abstract: This study uses standard synthetic methodologies to produce tissue-mimicking materials that match the morphology and emulate the in vivo murine and human cardiac mechanical and imaging characteristics, with dynamic mechanical analysis, atomic force microscopy (AFM), scanning electron microscopy (SEM) and magnetic resonance imaging. In accordance with such aims, poly(glycerol sebacate) (PGS) elastomeric materials were synthesized (at two different glycerol (G)-sebacic (S) acid molar ratios; the first was synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The presented work shows that emulation and study of cardiac motion is possible in computer-controlled human and scalable rodent heart phantoms. In addition to commercially used PVA and urethane elastomeric materials, it is also shown that recently synthesized biocompatible PGS materials possess mechanical properties (bulk and surface elasticity; as assessed by DMA measurements) (38,43) that can potentially match the bulk mechanical properties of the in-vivo heart (rat Young Moduli values range between 0.001 and 0.14 MPa and human values between 0.02 and 0.5 MPa) (6,(44)(45)(46)(47)(48)(49)(50)(51)(52). Experimental work with AFM independently confirmed the graded surface stiffness of most of the commercially available elastomers (C-E).…”
Section: Discussionmentioning
confidence: 99%
“…The presented work shows that emulation and study of cardiac motion is possible in computer-controlled human and scalable rodent heart phantoms. In addition to commercially used PVA and urethane elastomeric materials, it is also shown that recently synthesized biocompatible PGS materials possess mechanical properties (bulk and surface elasticity; as assessed by DMA measurements) (38,43) that can potentially match the bulk mechanical properties of the in-vivo heart (rat Young Moduli values range between 0.001 and 0.14 MPa and human values between 0.02 and 0.5 MPa) (6,(44)(45)(46)(47)(48)(49)(50)(51)(52). Experimental work with AFM independently confirmed the graded surface stiffness of most of the commercially available elastomers (C-E).…”
Section: Discussionmentioning
confidence: 99%
“…Within the realm of SC therapies (including SC-enriched scaffolds, passive 2D-explant membranes [30], 3D extracellular-matrix [ECM] or other biomimetic materials [19,[128][129][130][131], and artificial organs [18]), non-invasive imaging and tracking of labelled cells and their functional impact have taken leading and prominent roles in recent years (Fig. 4).…”
Section: Image-based Labeling and Tracking Of Stem-cells And Stem-celmentioning
confidence: 99%
“…In the pursuit of these approaches, increased interest has been documented for identification of biomimetic materials that match local tissue morphology, and mechanical [13,186] and imaging properties [13,187]. As reported by Kossivas et al [130], polymeric or elastomeric materials have traditionally been locally injected or attached and have been found to possess biocompatibility and bioactivity properties that facilitate good adhesion with the surrounding environment, ensuring mechanical stability and proper structural moduli [13], withstanding static and dynamic loading [188]. Recent studies have investigated different classes of scaffold biopolymers as passive epicardial restraint bio-artificial membranes in IHD [13,189] or for controlled delivery of SCs, with and without preconditioning, such as electromechanically synchronous stimulation [187,190].…”
Section: Mr Image-based Homogeneous Membrane and Organ Development Usmentioning
confidence: 99%
See 1 more Smart Citation
“…Validation of data obtained by nanoindentation experiments varies and primarily depends on the substrate, instrument condition, and environment used for experiments. Substrates such as glass cover slips, tissue culture polystyrene, chlorapatite single crystals, uncoated or coated with fibronectin/collagen I, poly(glycerol sebacate) elastomers, and poly(lactic‐ co ‐glycolic acid) (PLGA), are conventionally used in nanoindentation procedures. Human cells respond via alterations in their mechanics to the synthetic and biological substrate to which they adhere .…”
Section: Nanoindentation Function and Factors Affecting Mechanical Prmentioning
confidence: 99%